Perubahan Hunian Tradisional Suku Dayak Bukit di Kalimantan Selatan (Kajian Perubahan dengan Metode Etnografi) - Bani Noor M; Tony Atyanto D; Arya Ronald; Heddy Shri Ahimsa-Putra (Forum Teknik, 2013)
This paper explains the change of Dayak Bukit's dwelling in the Meratus Mountain in South Kalimantan Province, Indonesia. This research utilized naturalistic paradigm based on the axioms of the nature of reality. By focusing the study on local people, this research employed ethnography met, .od, particularly domain analysis. Interpretation of the domain came into the result that balai-adat is one of the shelters of Dayak Bukit tribes. Currently, Dayak Bukit tribes do not live in a communal dwelling anymore, but live in scuttered housing. Consequently, the function of balai-adat shift from a dwelling into a place of ceremony and cultural activities. It is concluded that balai-adat is an identity of the groups and it corltributes to maintain the existence and the representation of the structure of the Bukit Dayak tribes.Keywords: dwelling change, balai-adat, Dayak Bukit tribes, identity of the groups.